Longitudinal ultrasonographic assessment of placentome diameter and maternal ovine placental lactogen across gestation in sheep - Baykal, Kerem; Sabuncu, Ahmet; Evkuran Dal, Gamze; Enginler, Sinem Özlem; Baykal Uğur, Aslıhan; Yılmaz, Merve; Sarılar, Mert (Frontiers in Veterinary Science, 2026)
IntroductionPlacental development in sheep involves closely coordinated morphological and endocrine processes. Ultrasonographic placentome measurements and maternal ovine placental lactogen (oPL) profiles reflect distinct components of pregnancy progression; however, their longitudinal relationship across gestation has not been clearly defined. This study aimed to characterize temporal changes in placentome diameter and maternal oPL concentrations and to evaluate how their association evolves throughout pregnancy.MethodsFifty clinically healthy, multiparous Kivircik ewes carrying singleton pregnancies were monitored longitudinally from Day 26 to Day 145 of gestation. Serial transabdominal ultrasonography was performed at two-week intervals to measure placentome diameter using consistent anatomical landmarks. Maternal blood samples collected at each examination were analyzed for serum oPL concentrations using validated immunoassays. Gestational changes were assessed using non-parametric repeated-measures analyses. Associations between structural and endocrine variables were examined using day-specific correlation analyses and within-ewe models that accounted for repeated observations and individual baseline variability.ResultsPlacentome diameter increased rapidly during early gestation, rising from approximately 1.3 cm at Day 26 to around 3.5 cm by mid-gestation, after which values stabilised and showed only minor fluctuations toward term. Maternal oPL concentrations increased progressively from early pregnancy, reaching peak values of approximately 15–16 μg/mL in late gestation before declining near parturition. No significant association between placentome diameter and oPL concentration was detected during early gestation. Transient inverse relationships were observed at selected mid-gestational time points, whereas from late gestation onward, a consistent positive association emerged. Within-ewe analyses demonstrated a strong positive co-variation between placentome diameter and circulating oPL concentrations after controlling for inter-individual differences.DiscussionThese findings indicate that placentome growth and oPL secretion follow distinct yet interrelated developmental trajectories during sheep gestation, with increasing structural–endocrine concordance in late pregnancy. The integrated longitudinal evaluation of placentome biometry and maternal oPL profiles provides a refined framework for interpreting placental development and may support improved assessment of gestational progression in both research and clinical settings.